Study on the Image Construction of Korean Popular Talk Show Variety Artists: Taking Nothing Much Prepared as an Example - Jiang, Yuhan (International Journal of Social Sciences and Public Administration, 2024)
As an extremely important part of the development of Korean pop culture represented by the Korean "idol" industry, the artiste image is supported and loved by a wide range of fans for its strong style, vibrant and visually appealing, and trend-setting beauty. As an entertainment medium in the new era, variety shows have also made a significant contribution to the development of the Korean cultural industry. Therefore, the image construction method that takes "the contrast of the artist's image" as the main entry point can maximally amplify the artist's own charismatic focus under the angle of variety show shooting, especially under the interview nature of the conversation camera, which not only allows the audience to understand and comprehend the artist, but also gives the artist a space for better emotional communication with the fans. It also gives the artiste a space to communicate with their fans emotionally.